1995
DOI: 10.1143/jjap.34.l1344
|View full text |Cite
|
Sign up to set email alerts
|

Ce4+: a New Etching Agent for Cadmium Telluride

Abstract: Cadmium telluride (CdTe) has been etched for the first time in a 2M H2SO4 solution in the presence of Ce4+. The etching rates have been obtained by means of step measurements. They are proportional to the Ce4+ concentration and to the dipping time and are close to etching rates obtained for III-V compounds under the same conditions. The etching rates show no decrease with time in the concentration range studied ( 10-4 M-10-1 M) even for large steps (several µ m). Etching rates up to 0.1 µ m/min have been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…''Electroless'' oxidation has been widely described on III-V and II-VI semiconductor (SC) interfaces. These works showed that using oxidizing agents with standard potentials close to the valence band (VB) position of the material, the reduction of the oxidizing agent by holes injection and the oxidation of the SC take place simultaneously on the same surface [19][20][21][22][23]. In a previous work, the ''electroless'' oxidation of as-deposited polycrystalline boron-doped diamond (BDD) films, using four different oxidizing solutions at room temperature, Ce 4+ , MnO 4…”
Section: Introductionmentioning
confidence: 99%
“…''Electroless'' oxidation has been widely described on III-V and II-VI semiconductor (SC) interfaces. These works showed that using oxidizing agents with standard potentials close to the valence band (VB) position of the material, the reduction of the oxidizing agent by holes injection and the oxidation of the SC take place simultaneously on the same surface [19][20][21][22][23]. In a previous work, the ''electroless'' oxidation of as-deposited polycrystalline boron-doped diamond (BDD) films, using four different oxidizing solutions at room temperature, Ce 4+ , MnO 4…”
Section: Introductionmentioning
confidence: 99%
“…We investigate the "electroless" oxidation of asdeposited polycrystalline BDD films in oxidizing solutions at room temperature. "Electroless" oxidation has been widely studied on III-V and II-VI semiconductor (SC) interfaces [5][6]. These works showed that using oxidizing agents with very positive standard potentials (V°ox/red) close to the valence band (VB) position of the material, the reduction of Ox + by holes injection in the Valence Band and the oxidation of the SC can take place simultaneously on the same surface.…”
mentioning
confidence: 99%
“…Current-voltage measurements with Rotating Disk Electrode (RDE) were also performed to study the reduction mechanism of Ce 4+ and Fe(CN) 6 3oxidizing molecules at Diamond surfaces.…”
mentioning
confidence: 99%